Nitrifying biomass can retain its acclimation to 2, 4, 6-trichlorophenol. (15th October 2020) - Zou, Shasha; Zhang, Yongming; Chen, Fu; Yu, Xiyin; Wu, Xueqi; Zhang, Chenyuan; Rittmann, Bruce E.
Highlights: Acclimated nitrifying biomass could resist inhibition from TCP exposure. "Memory" of the acclimated nitrifying biomass to TCP was discovered. The biomass still resisted inhibition when TCP suddenly was added after two months. Sub-cultured biomass inherited and retained the ability to resist TCP inhibition. The abundance of bacteria able to resist TCP increased in the acclimated biomass. Abstract: Many municipal wastewater treatment plants in China receive industrial wastewater that contains inhibitory organic chemicals, such as chlorinated phenols. For the common aerobic biological treatment, nitrification is a key step, but nitrifying bacteria are notably sensitive to inhibition by chlorinated phenols. In this work, normal activated sludge (containing nitrifying biomass) was acclimated to 2, 4, 6-trichlorophenol (TCP). The acclimated biomass had more than 2-fold faster nitrification kinetics than normal biomass when exposed to TCP, and it also achieved effective TCP removal in parallel. When suddenly exposed to TCP after as much as two months without TCP input, the acclimated nitrifying biomass retained effective nitrification and TCP biodegradation: The nitrification rate and TCP removal rate were 0.325 mM/h and 0.049 mM/h for the acclimated biomass, compared to only 0.165 mM/h and 0.001 mM/h for normal biomass. Resistance to TCP inhibition also was retained for 5 generations of sub-culturing without TCP exposure. High-throughput sequencing confirmed that the acclimated biomass contained nitrifying bacteria and heterotrophic bacteria capable of degrading TCP, although the key genera changed during sub-culturing. Graphical abstract: Image, graphical abstract